Childhood injury in Tower Hamlets: Audit of children presenting with injury to an inner city A&E department in London. Issue 6 (June 2015) - Smith, Dianna; Kirkwood, Graham; Pott, Jason; Kourita, Lida; Jessop, Vanessa; Pollock, Allyson M.
Abstract: Introduction: Childhood injury is a leading cause of mortality and morbidity worldwide with the most socio-economically deprived children at greatest risk. Current routine NHS hospital data collection in England is inadequate to inform or evaluate prevention strategies. A pilot study of enhanced data collection was conducted to assess the feasibility of collecting accident and emergency data for national injury surveillance. Aims: To evaluate the reliability and feasibility of supplementary data collection using a paper-based questionnaire and to assess the potential relationship between income deprivation and incidence of paediatric injury. Methods: Clinical staff conducted an audit of injuries in all patients under 16 years between June and December 2012 through completion of a questionnaire while taking the medical history. Descriptive statistics were produced for age, sex, time of arrival, activity at time of injury, mechanism and location of injuries. The association between known injury incidence and area level income deprivation (2010 English Index of Multiple Deprivation [IMD] Income Deprivation Domain from home postcode) was assessed using Spearman's rank correlation. Representativeness of the audit was measured using z -test statistics for time of arrival, age, sex and ethnicity. Results: The paper audit captured 414 (6.5%) of the 6358 under-16 injury-related attendances recorded on the NHS Care Record Service Dataset. Comparison of the audit dataset with NHS records showed that the audit was not representative of the larger dataset except for sex of the patient. There was a positive correlation between injury incidence and income deprivation measured using IMD score where data were available ( n  = 384, p  < 0.001). Nearly half of the attendances were due to falls, slips or trips (49.8%) and more than half were due to either leisure (32.9%) or sport (18.1%) activities. Conclusion: There is evidence of area level income inequalities in injury incidence among children attending the Royal London Hospital. The audit failed to capture a high proportion of cases, likely due to the paper-based format used. This study highlights the importance of routinely collecting enhanced injury data in computerized hospital admission systems to provide the necessary evidence base for effective injury prevention. The findings have contributed to plans for implementation.